Covering the Left: Abante Tonite’s Coverage on the “Enemies of the State” - Dela Cruz, Ma. Irish D. (Plaridel Journal of Communication, Media, and Society; Vol 5 No 2 (2008): Media and Governance, 2008)
This content analysis explores the reporting of Abante Tonite on issues concerning the “leftist” movement, i.e., the Communist Party of the Philippines (CPP) and its alleged front organizations tagged by the government as “enemies of the state”. Particularly, this study analyzes the treatment of events, topics, individuals, and groups that were covered by the tabloid from July 2005 to August 2006 (N=43 articles). Using framing analysis, findings show a stereotyped treatment of actors and topics: negative for the leftist movement and positive for the government. The negative treatment of the leftist movement translates into two primary modes of representation: first, as an organization to be feared because of its capability to wreak havoc among soldiers and civilians; and second, as a weak, disintegrating organization slowly losing its members in encounters with the military either by death, injury, capture, or surrender.